Quality of Life Assessment in Skin Tag Patients - Putra, Imam Budi; Jusuf, Nelva Karmila; Kartayana, Johan (Talenta Publisher, 2018)
Patients with skin disease may experience clinical symptoms, such as itching, pain, and discomfort, that can have a negative impact on quality of life (QOL). Skin tag is a common benign tumor of the skin with small, soft pedunculated protrusion, it commonly occures in axilla, neck and major flexura area, despitethe lesion usually asimptomatic, sometimes patients complain about cosmetics appereances, itching or discomfort experienced. Objective: The aim of our study was to assess the impact of skin tag lesion on quality of life of patients. Method: This is a descriptive study with a cross sectional design, involving 50 patients with skin tag lesion who visited the Dermatology outpatient clinic Adam Malik General Hospital, Medan from September 2016 to October 2016. The patients were filled Indonesian version of skindex-29 questionnaire to measures the effects of skin disorders on their QOL. Result: In this study QOL in skin tag patient was fairly good, 38(76%) subjects had a skindex-29 category score<5, and 12(24%) subjects had a skindex-29 score 6-17. We didn’t findimpaired QOL in all skin tag patients. Conclusion: In this study’s we concluded skin tag does not affect the quality of life of the patients.